Stress-induced galectin-1 influences immune tolerance in the spleen and thymus by modulating CD45 immunoreactive lymphocytes - Sasaguri, Kenichi (J Physiol Sci, 2016)
Galectin-1 (Gal-1) is differentially expressed in normal and pathological tissues and regulates immune cell homeostasis. Restraint stress increases serum Gal-1 in rats. However, the function of stress-induced Gal-1 in serum is unknown. We determined if stress-induced Gal-1 in serum accumulates in immunocompetent organs as protection from physiological and/or psychological stress. Western blotting showed that the intensity of Gal-1 bands in stressed groups was significantly higher than that in controls. RT–PCR analysis indicated that the Gal-1 mRNA level did not increase after restraint stress. The numbers of Gal-1 immunoreactive cells in the splenic periarterial lymphatic sheath (PLS) and the thymus medulla of the stressed group were increased compared with those in controls. Furthermore, stress-induced Gal-1 immunoreactive cells corresponded to CD45 immunoreactive lymphocytes (CD45(+)) in the PLS of the spleen and the medulla of the thymus. Thus, stress-induced Gal-1 immediately accumulates in the spleen and thymus, and may modulate the immune response through apoptosis by binding to CD45(+) lymphocytes in immune organs following physiological and/or psychological stress.